2001
DOI: 10.1023/a:1011126330233
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen dependent expression of the receptor tyrosine kinase axl in normal and malignant human breast

Abstract: Our results suggest that axl may serve as a mediator of estrogen stimulation preventing the completion of the breast epithelial life cycle and that estrogen induced axl expression may give a survival signal to cancerous cells, preventing them from dying through apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 28 publications
5
70
2
1
Order By: Relevance
“…In addition, correspondingly, many hemopoietic cell-specific genes such as CD34, lactoferrin, and myeloperoxidase are regulated by MZF1 (4, 51, 52), whereas very few genes of cell types of different origin (e.g., keratinocytes, osteoblasts) such as PADI 1 and N-cadherin are transactived by MZF1 (40,53). Axl is expressed in certain leukemia-type cells, but also in diverse solid tumors (22)(23)(24)(25)(26)(27), and excitingly, we found that the Axl gene promoter harbors multiple MZF1 motifs. Among them, mutation of the MZF1 motif at −479/ −473 bp reduced promoter activity most significantly, and additional combination mutations did not show considerably more reduction of activity, showing that this motif is the most relevant for Axl transactivation by MZF1.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, correspondingly, many hemopoietic cell-specific genes such as CD34, lactoferrin, and myeloperoxidase are regulated by MZF1 (4, 51, 52), whereas very few genes of cell types of different origin (e.g., keratinocytes, osteoblasts) such as PADI 1 and N-cadherin are transactived by MZF1 (40,53). Axl is expressed in certain leukemia-type cells, but also in diverse solid tumors (22)(23)(24)(25)(26)(27), and excitingly, we found that the Axl gene promoter harbors multiple MZF1 motifs. Among them, mutation of the MZF1 motif at −479/ −473 bp reduced promoter activity most significantly, and additional combination mutations did not show considerably more reduction of activity, showing that this motif is the most relevant for Axl transactivation by MZF1.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, we confirm that overexpression of MZF1 is tumorigenic, and for the first time, we report that MZF1 induces tumor growth and metastasis through the transactivation of Axl, thus adding to the molecular targets and mechanisms that can mediate an oncogenic potential of MZF1 in epithelialderived tissues. Axl has been reported as a transforming gene (21) that is overexpressed in several tumors (22)(23)(24)(25)(26)(27), and the Gas6/Axl signaling pathway is known to induce cell proliferation, antiapoptosis, migration, invasion, and angiogenic processes, which are most likely mediated through Ras, Src, mitogen-activated protein kinase/extracellular signal-regulated kinase, phosphoinositide 3-kinase/Akt, and NF-κB signaling pathways (14,15,19,29,31,32,(44)(45)(46)(47)(48)(49). However, still further studies are needed to enhance the understanding of the downstream components of the Gas6/Axl signaling axis in tumor formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The receptor tyrosine kinase Axl is expressed in multiple cell types, including breast epithelial cells, and can transform NIH 3T3 cells by activating PI3K and Src (21,22). As predicted by MS, Axl phosphorylation was seen in 3T3-Her2 cells and inhibited by PD168393.…”
Section: Her2mentioning
confidence: 74%
“…Dysregulation of Axl or its ligand Gas6 is implicated in the pathogenesis of a variety of human cancers. Overexpression of Axl has been reported in a wide array of human cancers (Craven et al, 1995;Ito et al, 1999;Berclaz et al, 2001;Sun et al, 2004;Shieh et al, 2005) and is associated with invasiveness and metastasis in lung (Shieh et al, 2005), prostate (Sainaghi et al, 2005), breast (Meric et al, 2002;Zhang et al, 2008), gastric (Wu et al, 2002) and pancreatic (Koorstra et al, 2009) cancers, renal cell carcinoma (Chung et al, 2003) as well as glioblastoma (Hutterer et al, 2008). Recently, by profiling of phosphotyrosine signaling, activated Axl protein was detected in about 5% primary tumors of non-small-cell lung cancer (NSCLC) (Rikova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%